2014
DOI: 10.7717/peerj.626
|View full text |Cite
|
Sign up to set email alerts
|

Chicks change their pecking behaviour towards stationary and mobile food sources over the first 12 weeks of life: improvement and discontinuities

Abstract: Chicks (Gallus gallus domesticus) learn to peck soon after hatching and then peck in rapid bursts or bouts with intervals of non-pecking activity. The food sources may be static such as seeds and chick crumb, or mobile such as a mealworm. Here, changes with age in pecking toward chick crumb and a mealworm were measured.Chicks were reared in pairs and their pecking of crumb food was video recorded in their pair housed environment, from food presentation, every third day from day 8 (wk 2) to day 65 (wk 10). Peck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Providing live BSFL in tubes resulted in a large amount of time spent interacting with these tubes, and we observed that the interaction consisted mainly of pecking and scratching at the tubes (Supplementary Video S1). Pecking at the ground or at objects is a natural behaviour of chickens 40 , therefore performing this behaviour could satisfy a motivational need of broilers. Interacting with a plastic tube might be less natural for broilers, though broilers were clearly motivated to interact with the tubes as reflected by the large amount of time they spent performing foraging-related behaviour directed towards the tubes.…”
Section: Measurementioning
confidence: 99%
“…Providing live BSFL in tubes resulted in a large amount of time spent interacting with these tubes, and we observed that the interaction consisted mainly of pecking and scratching at the tubes (Supplementary Video S1). Pecking at the ground or at objects is a natural behaviour of chickens 40 , therefore performing this behaviour could satisfy a motivational need of broilers. Interacting with a plastic tube might be less natural for broilers, though broilers were clearly motivated to interact with the tubes as reflected by the large amount of time they spent performing foraging-related behaviour directed towards the tubes.…”
Section: Measurementioning
confidence: 99%
“…We hypothesize that the uneven accumulation of CuSO 4 in the bedding material from different parts of turkey shed could be a reason of difference in mortality. Another possible explanation could be the difference in foraging behavior between males and females (Murphy et al, 2014; Fernandes et al, 2015). In this paper, we have described cases of acute Cu toxicosis in turkeys after the ingestion of bedding contaminated with CuSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Providing live BSFL in tubes resulted in a large amount of time spent interacting with these tubes, and we observed that the interaction consisted mainly of pecking and scratching at the tubes. Pecking at the ground or at objects is a natural behaviour of chickens (Murphy et al, 2014), therefore performing this behaviour could satisfy a motivational need of broilers. Interacting with a plastic tube might be less natural for broilers, though broilers were clearly motivated to interact with the tubes as reflected by the large amount of time they spent performing foraging-related behaviour directed towards the tubes.…”
Section: Discussionmentioning
confidence: 99%